2015
DOI: 10.2172/1179210
|View full text |Cite
|
Sign up to set email alerts
|

Flowsheet Testing for Strip Effluent to Slurry Mix Evaporator Modifications at the Defense Waste Processing Facility

Abstract: Savannah River Remediation plans to add strip effluent to the Sludge Receipt and Adjustment Tank (SRAT) and/or the Slurry Mix Evaporator (SME) during processing in the Defense Waste Processing Facility (DWPF). At the present time, strip effluent is added only to the SRAT, but this flowsheet change is planned to allow more flexibility in processing the large volume of strip effluent produced by the Modular Caustic-side Solvent Extractant Unit (MCU) or the Salt Waste Processing Facility (SWPF).Four process demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…A study was completed by SRNL to evaluate whether the addition of SEFT in the SME cycle would have any influence on nitric-formic Acid Flowsheet CPC processing. 3 This testing was designed to bound all future DWPF processing, so it included high noble metal concentration (HM or H Modified) and high SEFT addition volume (38,000 gallons, 8,000 in SRAT, 30,000 in SME). The report recommended "Based on the testing completed, an endorsement of the flowsheet change for adding strip effluent to the SME is not currently warranted."…”
Section: Nitric-formic Acid Flowsheet Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study was completed by SRNL to evaluate whether the addition of SEFT in the SME cycle would have any influence on nitric-formic Acid Flowsheet CPC processing. 3 This testing was designed to bound all future DWPF processing, so it included high noble metal concentration (HM or H Modified) and high SEFT addition volume (38,000 gallons, 8,000 in SRAT, 30,000 in SME). The report recommended "Based on the testing completed, an endorsement of the flowsheet change for adding strip effluent to the SME is not currently warranted."…”
Section: Nitric-formic Acid Flowsheet Experimental Resultsmentioning
confidence: 99%
“…2 The addition of SE to the SME has been previously studied for the nitric-formic acid flowsheet. 3 This study found that due to the long processing time that results from processing increased volumes of SE may lead to higher hydrogen generation, higher ammonia production, higher formate destruction, lower REDOX ratio, higher potential for foaming and coil fouling, and higher yield stress and consistency. As a result of this testing, the addition of SE to SME was not implemented in DWPF.…”
Section: Introductionmentioning
confidence: 84%
“…Testing has been performed for the nitric-formic flowsheet using the SEFT from either the baseline (i.e., BOBCalixC6), the Next Generation Solvent (NGS) (i.e., MaxCalix b ), and the blended solvent systems. 2 Since Sludge Batch (SB) 3, 3 SRNL has performed testing specific to ARP as part of nitric-formic flowsheet testing with simulants. Simulated ARP streams typically added less monosodium titanate c (MST) to the slurry than the SWPF version of AR.…”
Section: Table Of Contentsmentioning
confidence: 99%
“…The first test listed is the evaluation performed for the nitric-formic flowsheet on the inclusion of SEFT material in the SME. 2 Processing difficulties were encountered with heat transfer rod fouling specific to the experimental system that ultimately led to increased hydrogen generation. Lab scale testing simulated a total of 38,000 gallons of SEFT material processed during these cycles split between the SRAT and the SME, for a respectable 80 hour boiling time.…”
Section: Testing Backgroundmentioning
confidence: 99%
See 1 more Smart Citation